Intrathecal Baclofen in Patients With Persistent Vegetative State: 2 Hypotheses - Sarà, Marco; Pistoia, Francesca; Mura, Elisa; Onorati, Paolo; Govoni, Stefano (Archives of physical medicine and rehabilitation, 2009)
Sarà M, Pistoia F, Mura E, Onorati P, Govoni S. Intrathecal baclofen in patients with persistent vegetative state: 2 hypotheses. Sporadic cases of recovery from persistent vegetative state (PVS) after administration of intrathecal baclofen (ITB) have been reported without giving any possible explanation for its paradoxical effect. We summarize our recent findings on 5 patients with PVS treated with ITB and make some speculations on the mechanisms responsible for the observed clinical improvement. The patients developed spasticity and were judged eligible for ITB therapy. Two weeks after pump implantation, patients began to show a clinical improvement that, at the end of the 6 months' follow-up, was stable in all but 1 patient, ranging from a mere increased alertness to a full recovery of consciousness, as revealed by changes of the Coma Recovery Scale–Revised (CRS-R) score. Our findings suggest that ITB might favor a variable degree of clinical improvement. A proposal for a pharmacodynamic explanation of this effect has not been formally put forward. We hypothesize 2 possible mechanisms: first, a modulation confined to spinal cord segmental activities and to neuronal centripetal outputs reaching the cortex; and second, a modulation of sleep-wake cycles that, although present, may be dysregulated and interfere with alertness and awareness. Although our research is confined to a few subjects, it provides follow-up information by means of the CRS-R that is a validated standardized neurobehavioral instrument expressly designed for use in patients with PVS. Our observations indicate that further systematic investigation of the mechanisms and the putative clinical applications of ITB should be undertaken.